PENGARUH HARGA, PELAYANAN, LOKASI, DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA HYPERMART PURI INDAH DI JAKARTA BARAT - A, Mimi S; Daniaty, Feliciana (Jurnal Ekonomi, 2017)
This study was conducted to determine the effect of price, service, location and diversity of products on purchase decisions on Hypermart Puri Indah, West Jakarta. The population in this study are consumers who shop at Hypermart Puri Indah. In this study took a sample of 100 respondents. The method used in this study is a convenience sampling method non - probabilistic findings of this study indicate that the price, service, location and product diversity significantly influence purchasing decisions at Hypermart